Efektivitas Program Arabic Supercamp Dalam Meningkatkan Keterampilan Berbicara Bahasa Arab - Faruq, Muh.; Fauzi, Firman Nurul (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – This study aims to evaluate the effectiveness of an Arabic language camp in improving the Arabic speaking skills of students at MTsN 4 Malang, particularly in the Religious Program. The camp was conducted intensively over 8 instructional hours in 2 days using an interactive and immersive Arabic learning approach.Method – This study employed a quantitative approach using a Pre-Experimental Design one-group pretest–posttest design involving 30 student participants. An oral speaking test based on dialogue model was administered before and after the program. Due to non-normal data distribution, the Wilcoxon signed-rank test was used to assess statistical significance, followed by a normalized gain (N-Gain) analysis to measure learning improvement. Findings – The results showed an increase in the average score from 42 in the pretest to 78 in the posttest. The Wilcoxon test produced a significance value of p < .001 (?= .05), indicating a statistically significant improvement in students' Arabic speaking skills. The minimum N-Gain score was 0.30, the maximum was 1.00, and the average was 0.63, which is classified as moderate, suggesting the camp was moderately effective. Research Implications – This study suggests that short-term, intensive Arabic immersion programs can serve as engaging and effective alternatives for enhancing speaking skills in religious educational settings. The study’s limitations include the short intervention duration, the limited and homogeneous sample, and a sole focus on cognitive outcomes. Future research should involve more diverse participants, extended timeframes, and incorporate additional skills, as well as affective and psychomotor aspects, to provide a more comprehensive understanding of the camp’s impact on Arabic-speaking proficiency.